Quantification of Bactericidal Action of the Ethanolic Extract ofGarcinia kola Seeds Alone, and in Combination with the BrandedAntibiotic Septrin, on the Culture Isolates from Throat Irritation Patients by Bacterial Growth Kinetics (Biological Sciences - PJSIR, 2005)
The relationship of growth rates of Streptococcus pyogenes, isolated from patients with protracted throat irritations and tonsillitis, with Garcinia kola extract and the branded antibiotic Septrin was investigated. A steady state was obtained shortly after the addition of Septrin, whereas a lag phase of about five generations elapsed for G. kola. The inhibitory effect of Septrin was about five times greater than the effect of G. kola. The inhibitory effect of G. kola was only bacteriostatic, whereas Septrin caused bacterial death if a certain threshold of concentration (1 mg) was passed, as evidenced by a decrease in the number of bacterial cells. Combination of Septrin and G. kola at concentrations where both acted merely bacteriostatically, led to effects considerably greater than would be expected from simple additivity. It is justifiable to conclude that the combination of G. kola extract and Septrin had a synergistic effect.